Smokeless Tobacco in Uganda: Perceptions among Tobacco Control Stakeholders - Male, Denis; Kansabe, Shirley; Lukwata, Hafsa; Rubanga, Alexander; Siddiqi, Kamran; Bauld, Linda; McNeill, Ann; Dobbie, Fiona (MDPI AG, 2022)
Abstract The use and sale of smokeless tobacco (SLT) is prohibited in Uganda under the Tobacco Control Act (TCA), 2015. Nonetheless, SLT products remain available, and there are limited and inconsistent data on SLT users. Additionally, the perceptions of tobacco control stakeholders on SLT are unknown, making it difficult to determine barriers to enforcing the ban. This study examined perceptions of tobacco control stakeholders regarding SLT in Uganda. Qualitative semi-structured interviews were conducted with stakeholders who were purposively selected from ministries, semi-autonomous government agencies and Civil Society Organizations. Interviews explored knowledge, attitudes, perceptions of SLT appeal, and user demographics. Data were analysed using Nvivo V.12 software. Participants demonstrated a general lack of awareness of SLT product types and the extent of their use. They believed SLT use was increasing among females and minors and was as harmful to health and the economy as smoking. SLT products were thought to be cheaper than cigarettes and to appeal to minors. Discreet use was thought to help users overcome the cultural aversion towards tobacco use among women and youth in Uganda. There is an urgent need to strengthen the implementation of the SLT ban whilst also increasing efforts to reduce tobacco smoking.
Keywords: smokeless tobacco; law enforcement; stakeholder perception; illicit trade; comprehensive ban